Muscle Contraction Regulates BDNF/TrkB Signaling to Modulate Synaptic Function through Presynaptic cPKCα and cPKCβI - Hurtado, Erica; Cilleros, Víctor; Nadal, Laura; Simó, Anna; Obis, Teresa; Garcia, Neus; Santafé, Manel M.; Tomàs, Marta; Halievski, Katherine; Jordan, Cynthia L.; Lanuza, Maria A.; Tomàs, Josep (Frontiers in Molecular Neuroscience, 2017)
The neurotrophin Brain-derived neurotrophic factor (BDNF) acts via tropomyosin-related kinase B receptor (TrkB) to regulate synapse maintenance and function in the neuromuscular system. The potentiation of ACh release by BDNF requires TrkB phosphorylation and Protein Kinase C (PKC) activation. BDNF is secreted in an activity-dependent manner but it is not known if pre- and/or postsynaptic activities enhance BDNF expression in vivo at the neuromuscular junction (NMJ). Here, we investigated whether nerve and muscle cell activities regulate presynaptic conventional PKC (cPKCα and βI) via BDNF/TrkB signaling to modulate synaptic strength at the NMJ. To differentiate the effects of presynaptic activity from that of muscle contraction, we stimulated the phrenic nerve of rat diaphragms (1 Hz, 30 min) with or without contraction (abolished by µ-conotoxin GIIIB). Then, we performed ELISA, Western blotting, qRT-PCR, immunofluorescence and electrophysiological techniques. We found that nerve-induced muscle contraction (1) increases the levels of mature BDNF protein without affecting pro-BDNF protein or BDNF mRNA levels; (2) downregulates TrkB.T1 without affecting TrkB.FL or p75 neurotrophin receptor (p75) levels; (3) increases presynaptic cPKCα and cPKCβI protein level through TrkB signaling; and (4) enhances phosphorylation of cPKCα and cPKCβI. Furthermore, we demonstrate that cPKCβI, which is exclusively located in the motor nerve terminals, increases activity-induced acetylcholine release. Together, these results show that nerve-induced muscle contraction is a key regulator of BDNF/TrkB signaling pathway, retrogradely activating presynaptic cPKC isoforms (in particular cPKCβI) to modulate synaptic function. These results indicate that a decrease in neuromuscular activity, as occurs in several neuromuscular disorders, could affect the BDNF/TrkB/PKC pathway that links pre- and postsynaptic activity to maintain neuromuscular function.